Dynamic Effects of Embedded Macro-Fiber Composite Actuators on Ultra-Light Flexible Structures of Repeated Pattern- a Homogenization Approach - A. Salehian; T.M. Seigler (Shock and Vibration)
Motivated by deployable satellite technology, this article presents a homogenization model of an inflatable, rigidized lattice structure with distributed macro-fiber composite (MFC) actuation. The model is based upon a general expression for the strain and kinetic energy of a fundamental repeated element of the structure. These expressions are reduced in order and expressed in terms of the strain and displacement components of an equivalent one-dimensional vibration model. The resulting model is used to analyze changes in the structural natural frequencies introduced by the local effects of the added macro-fiber composite actuators for several configurations. A finite element solution is used as a comparison for the homogenization model, and the two are shown to be in good agreement, although the latter requires significantly less computational effort.